BUDAYA BELAJAR SATU JAM BERSAMA BUKU SANTRI DI PONDOK PESANTREN SALAFIYAH-SYAFI`IYAH SUKOREJO SITUBONDO - Junaidi, Junaidi; Hidayat, Afif (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2022)
Pesantren literacy, both reading, ethics, and writing culture must be appreciated as the first step in freeing the country from the constraints of poverty on the one hand and moral crisis on the other. Because in fact, the progress of a nation starts from a love of literacy that transforms into a culture of literacy that is deeply rooted through continuity every time. In this study focused pesantren literacy in the frame of a series of reading activities an sich. (1) Implementation of One Hour Activities with Books at Pondok Pesantren Salafiyyah Syafi'iyyah Sukorejo Situbondo as an effort to increase the reading interest of students who are guided directly by the Head of Room and the seniority of the room in collaboration with relevant pesantren stakeholders and the final result of the One Hour Activity With Books as a Santri Learning Culture at Pondok Pesantren Salafiyyah Syafi'iyah Sukorejo Situbondo is the birth of interest in reading sukorejo students on the one hand and the increase in the increase santri on the other side.